Improving Learning Motivation and Physics Student Learning Outcomes Through Lesson Study Class XKR3 SMK N 3 Yogyakarta - Warnoto (Amanah: Jurnal Amanah Pendidikan dan Pengajaran, 2020)
Abstract This Action Research aims to improve learning motivation and physics learning outcomes of students in XKR3 class of SMK Negeri 3 Yogyakarta through Lesson Study in learning Fluid and Wave Competence Physics. This research was conducted in two cycles, each cycle consisting of 2 meetings, each meeting with an allocation of 3 lesson hours. Every meeting with Lesson Study includes: plan, do, see. Each cycle includes four steps, namely planning, action, observation and reflection. The results showed that the increase in motivation to learn in the first cycle amounted to 83.33%, in the second cycle amounted to 88.89% an increase of 5.56%. The increase in the achievement of the pre-cycle average learning outcomes 46.67, the first cycle an average of 55.71 complete 34.29%, the second cycle an average of 66.25, complete 37.5%. This research is 2 cycles, because in cycle II, learning motivation is more than 85%, and learning outcomes are more than 35%, Lesson study needs to be applied and continued in learning because of an increase in both learning motivation and learning achievement.